A stock policy system in a warehouse system: A system dynamics approach - Albal, Özgür (My University, 1999)
Büyük bir markanın yan kuruluşu olan ve çok fazla mal çeşidinin bulunduğu bir sistemde - FORD OTOSAN Yedek Parça Dağıtım Merkezi Deposu gibi - optimal stok seviyelerinin belirlenmesi önemli bir problem teşkil etmektedir. Bu tezin amacı da bu probleme bir çözüm getirmektir. Bu amaçla yapılan ilk şey yeni bir talep tahmin sistemi geliştirmek olmuştur. Visual Basic 4.0 da en sık kullanılan talep tahmin yöntemleri modellenmiştir. Daha sonra pek çok parçanın bulunduğu bu sisteme en iyi uyacak bir stok kontrol politikası seçildi: Periyodik Gözden Geçirme Stok kontrol Politikası. Hem zaman hem de para açısından bu sistemin binlerce parçanın bulunduğu bu sistemde etkin bir çözüm olacağına karar verilmiştir. Bu çalışmalarda temel amaç envanter taşıma seviyelerini belirlemek olmuştur. Kesikli çözüm yaklaşımları, bu tür sürekli sistemlerde sağlıklı bir çözüm olmayacağından dinamik çözümler bulunmaya çalışılmıştır. Maximum envanter seviyesi ve optimal gözden geçirme süresi Sistem Dinamiği Yaklaşımı ile bulunmaya çalışılmıştır. Bu Stella 5.1.1 software ortamında gerçekleştirilmiştir. Yeni sistem tahmini toplam maliyeti ve gelir ile sunulmuştur. Ve sonuç olarak eski ve yeni sistemler envanter maliyetleri açısından kıyaslanmıştır. Bütün bu çalışmaların detayları bu tezin ilgili bölümlerinde sunulmuştur. Determining optimal stock levels constitutes a considerable problem in a system where there are lots of part types, such as FORD OTOSAN Spare Parts Distribution Centre’s Warehouse as the distributor and partner of Ford which is one of the major brands in automotive sector. Thus, the aim of this thesis is to bring a solution to this problem. The first thing that was done in this thesis was to develop a new demand forecasting system. To bring a generic solution to this forecasting problem, a forecasting program is designed in Visual Basic 4.0 with widely used forecasting techniques in today’ s industry. Then a stock control policy that suits best to such a situation has been chosen (Periodic Review Inventory Control Policy) for its effectiveness in both time and money concerns in such a system of thousands of parts. The main purpose in doing this is to decide the inventory carrying level of thousands of parts that could be classified in identified groups. Since discrete solution approaches would not give realistic results in such a continuous system, dynamic property of the system is tried to be evaluated. To solve the stock problem appropriate maximum inventory levels and optimum review periods tried to be identified by using System Dynamics Approach as an effective system used in modelling dynamic systems. This is done in Stella 5.1.1 environment. The new system is presented with its expected total cost and profit values and the results of designed system is compared with the previous system by taking into consideration the total amount of inventory that is carried in both system - because only total inventory carried figures are available. Details of all these studies are presented in relevant sections of this thesis.
Keywords: STOK KONTROLÜ,BİLGİSAYAR DEST